Membrane fouling and flux reduction of Nannochloropsis sp protein hydrolysate using cross-flow ultrafiltration membrane - Md Saleh, Nur Izzati; Wan Ab Karim Ghani, Wan Azlina; Mustapa Kamal, Siti Mazlina; Alias, Azil Bahari; Harun, Mohd Razif (National University of Malaysia, 2026)
Microalgae protein hydrolysate enriched in peptide was produced by the enzymatic hydrolysis of Nannochloropsis sp. To obtain smaller peptides fractions, an ultrafiltration membrane was used to fractionate the hydrolysate, which contained a wide range of peptide sizes. However, a significant limitation of ultrafiltration membranes is flux reduction time due to fouling. This study investigates the influence of operational parameters variables such as flow rate, transmembrane pressure and pH on flux reduction and membrane fouling behaviour. Three membrane configurations (10 kDa, 5 kDa and two-stage 10/5 kDa) were evaluated. Kumar’s pore-blocking models were applied to the optimal configuration with the largest permeate flux to analyse fouling mechanism. The results showed that permeate flux was declined over time and stabilized within 20 to 35 minutes under all conditions. The best performance for microalgae protein hydrolysate fractionation was observed with two-stage 10/5 kDa membrane at a flow rate of 23 ml/min, TMP of 1.5 bar, and pH 2. The standard pore-blocking model effectively predicted the flux reduction, confirming the role of membrane fouling in performance decline. This study highlights that optimizing ultrafiltration membrane parameters and selecting the appropriate membrane configuration can mitigate fouling effects, enhancing flux stability and peptide transmission.